Continental Shift : A Journey Into Africa's Changing Fortunes - Bloom, Kevin and Poplak, Richard (London Portobello Books, 2016)
AFRICA IS FAILING. AFRICA IS SUCCEEDING. Africa is betraying its citizens. Africa is a place of starvation, corruption, disease. African economies are soaring faster than any on earth. Africa is squandering its bountiful resources. Africa is a roadmap for global development. Africa is turbulent. Africa is stabilising. Africa is doomed. Africa is the future. All of these pronouncements prove equally true and false, as South African journalists Richard Poplak and Kevin Bloom discover on their 9-year roadtrip through the paradoxical continent they call home. From pillaged mines in Zimbabwe to the creation of an economic marketplace in Ethiopia; from Namibia's middle class to the technological challenges facing Nollywood in the 21st Century; from China's investment in Botswana to the rush for resources in the Congo; and from the birth of Africa's newest country, South Sudan, to the worsening conflict in CAR, here are eight adventures on the trail of a new Africa. Part detective story, part report from this economic frontier, Continental Shift follows the money as it flows through Chinese coffers to international conglomerates, to heads of state, to ordinary African citizens, all of whom are intent on defining a metamorphosing continent.
Include Illustrations